POTENSI PROBIOTIK UNTUK MENCEGAH PENULARAN COVID-19 MELALUI PENINGKATAN KEKEBALAN TUBUH MANUSIA - Emma Riftyan; Usman Pato; Dewi Fortuna Ayu; Evy Rossi (Fakultas Pertanian Universitas Riau, 2021)
The COVID-19 pandemic, which initially began in Wuhan, China, quickly spread to more than 206 countries, including Indonesia. The use of vaccines is a preventive measure that is quite effective in preventing transmission of COVID-19. COVID-19 is caused by SARS CoV-2 which is the result of mutations from SARS-CoV which have higher virulence properties and spread faster. As of April 7, 2020, the number of infected people has reached more than 1,350,045 people including 76,328 people have died. Although there is no specific drug to treat COVID-19, administration of drugs such as remdesivir, fapilavir and chloroquin phosphate could cure 293,665 patients. In addition to therapeutic measures, preventive measures such as increased immunity are important steps to prevent transmission of various types of diseases. The results showed that probiotics could increase immunity through crosstalk between probiotics and intestinal mucosa. Interaction between probiotics and intestinal mucosa could increase the formation of lymphocytes (B and T cells), interleukin mainly IL-10 and IL-1β, immunoglobulins especially IgA, NK and Th-17 cells. The formation of this component will directly increase the body’s immune system against transmission of various diseases including COVID-19